EFFECT OF DIFFERENT HOUSING MANAGEMENT STRATEGIES ON PRODUCTION AND BEHAVIORAL RESPONSE OF BUFFALOES DURING DRY HOT SUMMER - U. Younas; M. Abdullah; J. A. Bhatti; T. N. Pasha; N. Ahmad; M. Junaid (Journal of Animal and Plant Sciences, 2018)
The current study was conducted with an aim to evaluate the effect of housing strategies on the production and behavioral responses of Nili-Ravi buffaloes during dry hot summer (May and June). The study was conducted at Buffalo Research Institute (BRI), Livestock Experiment Station (LES), Bhunike, Distt. Kasur, Punjab. Nili-Ravi buffaloes (n=20) with similar milk production and stage of lactation were selected from the herds maintained at LES, Pattoki. Buffaloes were divided into four different groups with 5 buffaloes in each group. Group A was kept under roof shade only (control); B was given anti-stress supplement (10gm, dry yeast powder; Saccharomyces cerevisiae); C under fans and group D buffaloes under fans with showers, provided with roof shades. Correspond to the temperature humidity index (THI) for May (85.6) and June (87.6), the daily milk production (MP; liter) was noticed significantly (P≤0.01) high in group D (7.33±0.10) as compared to animals in group A (6.39±0.13), B (6.52±0.09) and C (6.95±0.11). Similarly, dry matter intake (Kg; weekly) was high for group D (15.4±0.16; P≤0.05). However, cost per liter of milk production was lower for group D buffaloes. Group D buffalo’s performance was concluded best in terms of cost per liter of milk production.
Keywords: Buffalo; Milk production; Heat stress